Requilíbrio econômico-financeiro em contratos de arrendamento portuário: o caso do porto organizado de Paranaguá, no Estado do Paraná - Silva, Fabiane Tessari Lima da (2016)
Law number 12.815/2013, current legal guide of the port sector in Brazil, had as its most important innovation, the opening of competition to the port different terminals, exposed to numerous political regimes: private and public law. Furthermore, the sector of ports innovated by establishing that the element of delimitation of another regime is the polygonal design of the organized ports - task assigned to the Public Administration. As a result, terminals exposed to public law (operated by lessees) are now subjected to competition not originally advised and under uneven conditions, running the risk of having contractual divergences – as seen in some actual cases. Analyzing the parameters that advises the Administrators in the task of re-defying these polygonal – which determines the competitive environment –, we can come to the conclusion that the Organized Port of Paranagua' s lessees injured have assured the right to the immediate contractual re-balance.